Peran Pemerintah Desa dalam Pemberdayaan Masyarakat Petani Jagung di Desa Popayato - Wijayanti Wijayanti; Sukarman Kamuli; Roni Lukum (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of the village government in empowering corn farmers in Popayato Village, Pohuwato Regency. The village government, as the institution closest to the community, has a strategic responsibility in facilitating the development of local potential, particularly the corn farming sector, a leading regional commodity. This study used a qualitative approach with data collection techniques through interviews, observation, and documentation. The results indicate that the village government plays an active role as a facilitator, initiator, motivator, and mediator in various empowerment programs, such as agricultural extension, production input assistance, and strengthening farmer group institutions. However, obstacles remain, such as budget constraints, lack of cross-sector synergy, and minimal regeneration of young farmers. Therefore, ongoing commitment and inter-institutional cooperation are needed to realize sustainable farmer empowerment.